KEARIFAN LOKAL MELAYU SEBAGAI IDENTITAS KOTA BATAM - Danuwidjojo, Jusuf; Iood, Fandy; Sidabutar, Yuanita FD (Universitas Batam, 2021)
Indonesia is a country rich in local wisdom spread from Sumatera to Papua. The local wisdom has guided the community to live and survive in life. The local wisdom possessed by Indonesia is diverse, ranging from local wisdom in the field of Indonesian language and literature, the field of community life, agriculture and animal husbandry, the culinary field, the economic field, to the tourism sector. However, there are still many local wisdoms that have not been explored or recognized by the Indonesian people, especially the younger generation of the nation's successors. Describe Malay local wisdom as the identity of Batam City. The approach used is qualitative with descriptive analysis method. Malay local wisdom is at the core of the Malay tradition, a cultural strength and an important source of its human identity. Without local wisdom, Malays will lose their identity.